Effectiveness of Differentiated Learning Strategies with The Problem Based Learning Model in Improving Students’ Learning Outcomes - Agato, Lazarus; Sitompul, Stepanus Sahala; firdaus, Firdaus (Jurnal Pendidikan Fisika, 2025)
The topic of work and energy is one of the fundamental aspects of physics education, but many students have difficulty understanding its abstract concepts. This study explores the effectiveness of differentiated learning strategies combined with the Problem-Based Learning (PBL) model to improve students' understanding of work and energy at Sekadau Hilir State Junior High School 8. The research used a pre-experimental design with a one-group pretest-posttest approach, involving 36 eighth-grade students selected through purposive sampling. Data were collected through pre- and post-intervention tests and questionnaires, focusing on the student's conceptual understanding of the material. The intervention involved four sessions, with the PBL model tailored to students' individual learning styles. The results demonstrated a significant improvement in students' learning outcomes, as indicated by the posttest scores (mean = 82.22) compared to the pretest scores (mean = 33.47), with a p-value of 0.000, indicating a statistically significant difference. The effectiveness of the intervention was further supported by a high Cohen's effect size of 3.650, categorizing it as highly effective. The study concludes that differentiated learning, when integrated with the PBL model, effectively enhances students’ understanding of complex physics topics. This approach not only addresses diverse learning styles but also encourages active participation and problem-solving, making it a promising strategy for improving science education outcomes in junior high schools. Future studies should explore the broader application of this model to other physics topics to confirm its generalizability.